Engineering mechanics: statics - Leroy D. Sturges
Concurrent force systems-- Statics of particles-- Rigid bodies: equivalent force/moment systems-- Distributed forces: centroids and center of gravity-- Equilibrium of rigid bodies-- Trusses, frames and machines-- Internal forces in structural members-- Friction-- Second moments of area and moments of inertia-- Method of virtual work